Strategic management text and cases - Dess, Gregory G.; Lumpkin, G. T.; Eisner, Alan B.; McNamara, Gerry; Kim, Bongjin (McGraw-Hill Irwin, 2012)
Provides a treatment of traditional topics in strategic management. This title also offers thorough coverage of contemporary topics such intellectual assets, entrepreneurship, innovation, knowledge management, Internet strategies, crowdsourcing, environmental sustainability, businesses use of blogs and social networking sites and more.